Simulação de um trocador de calor casco e tubos com fluido turbulento utilizando código CFD - Alves, Bruna Almeida (2018)
In the execution of a design of a tube and shell heat exchanger, it is always necessary to analyze the ideal thermal design for the process in which it will be used. This analysis can be done in two ways: analytically, for simple and small heat exchangers, and using numerical computational simulation, for more elaborate exchangers. Computational Fluid Dynamics simulation using a commercial code has been widely disseminated and increasingly present in the academic environment because it is reliable, fast and inexpensive compared to experimental methods. The present work proposes to carry out the simulation in steady state through a commercial code, the Ansys CFX, of a tube and shell heat exchanger of the refinery of a corn mill processing. The interest is the validation of the computational method in front of the results of a tube and shell heat exchanger operation. The exchanger was analyzed using the turbulence model κ -ε, one of the most popular in the industry, and obtained very similar results to its operation.